Energy-Efficient Protocols for Massive IOT Connectivity in 6G Networks - Ravilla, Lokesh; Upadhyay, Satish; Louis, Magthelin Therase; Swain, Biswaranjan; Mamatha, G. N.; Mishra, Smita; Aneja, Aseem (International Journal of Engineering, Science and Information Technology, 2025)
The possible evolution in wireless communication as it approaches sixth-generation (6G) networks highlights remarkable features, including one of device connectivity, ultra-low latency, and energy efficiency, enabling mIoT deployment. However, these features come with a myriad of challenges with the integration of billions of constrained IoT devices, especially in relation to the aforementioned energy hurdles alongside scalability and spectrum efficiency. This work focuses on energy-efficient 6G IoT networks, proposing new low-power adaptive communication protocols, emphasising power adaptive performance, dependability, and trustworthiness. The roles of key facilitators, Reconfigurable Intelligent Surfaces (RIS), Non-Orthogonal Multiple Access (NOMA), machine learning coupled with energy harvesting, and even off-grid sustainable power sources are critical for enhanced sustainable connectivity. Covering the protocol design in the physical, MAC, and network layers permits the highlighting of cross-layer optimisation IoT ecosystems in 6G and the focused attention IoT research lacks, supporting bold, environmentally sustainable infrastructure designs.